Christianity and democracy: a theology for a just world order - De Gruchy, John W. (Cambridge studies in ideology and religion, 1995)
The need for global democratisation is now widely recognised, but there is considerable debate about what this means and how it can be achieved. In this important study John de Gruchy examines the historic and contemporary roles of Christianity in the development of democracy. He traces the gestation of modern democracy in medieval Christendom, and then describes the virtual breakdown of the relationship as democracy becomes the polity of modernity. Five twentieth-century case studies - the USA, Nicaragua, sub-Saharan Africa, Germany and South Africa - demonstrate the extent to which ecumenical Christianity has begun to reconnect with democracy and act as its contemporary midwife. De Gruchy argues that democracy needs to rediscover its spiritual heritage, while Christianity needs to develop a theology adequate for its participation in the realisation of a just democratic world order.